What do dust sinks tell us about their sources and past environmental dynamics? A case study for oxygen isotope stages 3–2 in the Middle Rhine Valley, Germany - Vinnepand, Mathias; Fischer, Peter; Hambach, Ulrich; Jöris, Olaf; Craig, Carol-Ann; Zeeden, Christian; Thornton, Barry; Tütken, Thomas; Prud'homme, Charlotte; Schulte, Philipp; Moine, Olivier; Fitzsimmons, Kathryn E.; et al. (E&G Quaternary Science Journal, 2023)
The study of geological archives of dust is of great relevance as they are directly linked to past atmospheric circulation and bear the potential to reconstruct dust provenance and flux relative to climate changes. Among the dust sinks, loess–palaeosol sequences (LPSs) represent the only continental and non-aquatic archives that are predominantly built up by dust deposits close to source areas, providing detailed information on Quaternary climatic and terrestrial environmental changes. Upper Pleistocene LPSs of western central Europe have been investigated in great detail showing their linkage to millennial-scale northern hemispheric climate oscillations, but comprehensive data on dust composition and potential source–sink relationships as well as inferred past atmospheric circulation patterns for this region are still fragmentary. Here, we present an integrative approach that systematically combines sedimentological, rock magnetic, and bulk geochemical data, as well as information on Sr and Nd isotope composition, enabling a synthetic interpretation of LPS formation. We focus on the Schwalbenberg RP1 profile in the Middle Rhine Valley in Germany and integrate our data into a robust age model that has recently been established based on high-resolution radiocarbon dating of earthworm calcite granules. We show that Schwalbenberg RP1 is subdivided into a lower section corresponding to late oxygen isotope stage 3 (OIS; ∼ 40–30 ka) and an upper section dating into the Last Glacial Maximum (LGM; ∼ 24–22 ka), separated by a major stratigraphic unconformity. Sedimentological proxies of wind dynamics (U ratio) and pedogenesis (finest clay) of the lower section attest to comparable and largely synchronous patterns of northern hemispheric climatic changes supporting the overall synchronicity of climatic changes in and around the North Atlantic region. The anisotropy of magnetic susceptibility (AMS) reveals a clear correlation between finer grain size and increasing AMS foliation within interstadials, possibly owing to ...